Assessment of academic/non‑academic factors and extracurricular activities influencing performance of medical students of Faculty of Medicine, Universiti Sultan Zainal Abidin, Malaysia - Haque, Mainul; A. Rahman, Nor Azlina; Majumder, Md Anwarul Azim; A Rahman, Nor Iza; Haque, Seraj Zohurul; Zulkifli, Zainal; Lugova, Halyna; Musa, Rabiu Muazu; Alattraqchi, Ahmed Ghazi (Wolters Kluwer - Medknow, 2018)
Background: Physical and mental comfort is known to have a crucial influence on health and performance amongst medical students. Very often, medical students suffer from poor quality of life (QOL) related to the work‑life balance due to the lack of sleep, nutritional and dietary disorders and low physical activity, resulting in a negative impact on their academic performance. This study aims to determine the potential academic/non‑academic factors and extra‑curricular activities influencing the performance of medical students in Universiti Sultan Zainal Abidin (UniSZA). Materials and Methods: This was a cross‑sectional study conducted on medical students at the Faculty of Medicine, UniSZA, Terengganu, Malaysia. A sample size of 300 respondents were recruited from Year I to V medical students. The questionnaire was adopted, modified and validated from a similar study in Saudi Arabia. Results: Majority of the students enjoy medical education are self‑motivated, have a good command of English, non‑smokers and have a sufficient sleep. Conclusion: University medical students possess good QOL within the optimum educational environment.